New insights into the structural analysis of maghemite and (MFe2O4, M = Co, Zn) ferrite nanoparticles synthesized by a microwave-assisted polyol process. (26th August 2020) - Gallo-Cordova, Álvaro; Espinosa, Ana; Serrano, Aida; Gutiérrez, Lucía; Menéndez, Nieves; del Puerto Morales, María; Mazarío, Eva
Abstract : A comprehensive structural analysis was presented on crystalline maghemite and ferrite (MFe2 O4, M = Co, Zn) nanoparticles prepared by the well-known polyol process enhanced by fast, reproducible, easy and efficient microwave heating. Abstract : The search for more efficient, scalable, reproducible and standardized synthesis methods able to control particle size and crystallinity is still a challenge in nanotechnology. The one-pot microwave-assisted polyol process has been optimized for the synthesis of well-defined ferrite nanoparticles. Highly uniform and crystalline γ-Fe2 O3, CoFe2 O4 and ZnFe2 O4 nanoparticles, with diameters below 14 nm have been prepared by an easy and reproducible one-pot microwave-assisted heating procedure in a polyol medium. A pure single phase and cubic spinel structure were confirmed by powder X-ray diffraction and Raman spectroscopy. Depending on the metal precursors, nanoparticles display magnetic features from superparamagnetic behaviour (Fe- and Zn-ferrites) to ferrimagnetism (Co ferrite) at room temperature. The iron oxidation state of 3+ and its short-range order coordination were studied by XAS (X-ray absorption spectroscopy). External field Mössbauer spectra, recorded at low temperature, confirmed the ferrimagnetic order with a Fe 3+ and M 2+ partial cationic distribution within both the A and B sites in zinc and cobalt ferrite, respectively. According to these results, the ferrite stoichiometry was (Zn0.70 Fe0.30 )[Zn0.30 Fe1.70 ]O4 and (Co0.28 Fe0.72 )[Co0.72 Fe1.28 ]O4 .